2012
DOI: 10.1002/pola.25907
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of free secondary amine bearing monomers by RAFT polymerization and other controlled radical techniques

Abstract: This work describes the polymerization of the free secondary amine bearing monomer 2,2,6,6‐tetramethylpiperidin‐4‐yl methacrylate (TMPMA) by means of different controlled radical polymerization techniques (ATRP, RAFT, NMP). In particular, reversible addition‐fragmentation chain transfer (RAFT) polymerization enabled a good control at high conversions and a polydispersity index below 1.3, thereby enabling the preparation of well‐defined polymers. Remarkably, the polymerization of the secondary amine bearing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 28 publications
1
92
0
Order By: Relevance
“…It has been reported that the extent of branching is higher 289 [186,187,229,577] 290 [175,203,305] 291 [211] 295 [308] 301 [165] 306 CSSQMA [389] 302 [164] 303 [209] 304 [305] 307 [578,579] 308 [579] 305 [212] 297 [188] 298 [201] 299 [201] 300 [387] 292 [189] 293 [173] 294 [210] Glycerol monomethacrylate Solketal methacrylate 296 [197,390] for conventional radical polymerization than for RDRP (ATRP, RAFT, and NMP). [443] A qualitative explanation was proposed in terms of the differences in the concentrations of short-chain radicals between RDRP and conventional radical polymerization.…”
Section: Acrylatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the extent of branching is higher 289 [186,187,229,577] 290 [175,203,305] 291 [211] 295 [308] 301 [165] 306 CSSQMA [389] 302 [164] 303 [209] 304 [305] 307 [578,579] 308 [579] 305 [212] 297 [188] 298 [201] 299 [201] 300 [387] 292 [189] 293 [173] 294 [210] Glycerol monomethacrylate Solketal methacrylate 296 [197,390] for conventional radical polymerization than for RDRP (ATRP, RAFT, and NMP). [443] A qualitative explanation was proposed in terms of the differences in the concentrations of short-chain radicals between RDRP and conventional radical polymerization.…”
Section: Acrylatesmentioning
confidence: 99%
“…[162] RAFT polymerization is not usually compatible with unprotected primary or secondary amines. Janoschka et al [209] have reported that RAFT polymerization can be successfully carried out in the presence of an unprotected hindered amine (2,2,6,6-tertramethylpiperidene) functionality in the methacrylate 194. However, the polymerization had to be conducted in aqueous ethanol as solvent (polymerization was not successful in toluene) and with a higher than usual concentration of initiator.…”
Section: Atrp-initiated Raft Polymerizationmentioning
confidence: 99%
“…Typically, nitroxides are often embedded in rings, like the six-membered ring of the TEMPO-radical [8][9][10][11][12] or the five-membered ring in the PROXYL-radical [14]. These radicals are often used in organic radical batteries [2,3,5,6,[8][9][10][11][12]15,16] and organic memory devices [17] because of their reversible redox-chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…These radicals are often used in organic radical batteries [2,3,5,6,[8][9][10][11][12]15,16] and organic memory devices [17] because of their reversible redox-chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation